Attacking the supply wagons to starve cancer cells to death. Issue 7 (22nd March 2016) - Selwan, Elizabeth M.; Finicle, Brendan T.; Kim, Seong M.; Edinger, Aimee L.
Abstract : The constitutive anabolism of cancer cells not only supports proliferation but also addicts tumor cells to a steady influx of exogenous nutrients. Limiting access to metabolic substrates could be an effective and selective means to block cancer growth. In this review, we define the pathways by which cancer cells acquire the raw materials for anabolism, highlight the actionable proteins in each pathway, and discuss the status of therapeutic interventions that disrupt nutrient acquisition. Critical open questions to be answered before apical metabolic inhibitors can be successfully and safely deployed in the clinic are also outlined. In summary, recent studies provide strong support that substrate limitation is a powerful therapeutic strategy to effectively, and safely, starve cancer cells to death. Abstract :